DURASI VENTILASI MEKANIK SEBAGAI FAKTOR RISIKO CEDERA GINJAL AKUT PADA PASIEN STROKE HEMORAGIK DI ICU: STUDI CASE-CONTROL - Qinxzy Yeremia Marbisuk Raja Panjaitan; Rahmadius Eka Santoso; Nopri Esmiralda (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Haemorrhagic stroke is a major cause of morbidity and mortality, especially in critical cases. Prolonged mechanical ventilation may increase the risk of systemic complications, including acute kidney injury (AKI). However, evidence on the association between ventilator duration and AKI in haemorrhagic stroke patients in Indonesia remains limited. This study aimed to analyse the relationship between ventilator use duration and AKI incidence in ICU-treated haemorrhagic stroke patients. Methods: This analytical observational study used a retrospective matched case-control design using medical records of patients with haemorrhagic stroke treated in the ICU from January 2023 to June 2025. A total of 206 eligible patients were included in this study. Data were analysed using univariate and bivariate tests (Chi-square), followed by conditional logistic regression with adjustment for age and sex in 37 groups (ratio 1:2). Results: A total of 125 patients (60.7%) developed AKI. The proportion of AKI was significantly higher in patients with ventilator use >7 days compared to ≤7 days (60.8% vs 39.2%; p < 0.001). Ventilator use >7 days increased the risk of AKI by 8.918 times(OR = 8.918; 95% CI 4.383–18.148). After controlling for age and gender, the association remained significant (OR = 5.848; 95% CI 2.331–14.673; p < 0.001). Conclusion: The duration of ventilator use is significantly and independently associated with the occurrence of AKI in patients with haemorrhagic stroke in the ICU, necessitating monitoring of renal function and AKI prevention strategies from the onset of intensive care. Keywords: Haemorrhagic stroke, ventilator, acute kidney injury, intensive care unit